PENGGUNAAN FACEBOOK DALAM KEGIATAN BELAJAR PESERTA DIDIK KELAS VIII SEKOLAH MENENGAH PERTAMA HARUNIYAH PONTIANAK - Afriyani, Nina; Wicaksono, Luhur; Lestari, Sri (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThe use of Facebook among adolescents today has grown rapidly and the facilities provided by Facebook for its users include creating a personal profile equipped with photos/pictures, a list of personal interests such as names, places of birth, home addresses, schools, hobbies and other personal information. Therefore, the researchers wanted to know more about the use of Facebook learning activities in class VIII students of SMP Haruniyah Pontianak.This study aims to obtain an overview of the use of facebook in learning activities in class VIII students of SMP Haruniyah Pontianak.The method used is descriptive method and the form of research is survey study. The population in this study were 80 students of class VIII of Pontianak HARUNIYAH Middle School. This study uses a quantitative approach. Data collection techniques used are indirect communication techniques with data collection tools in the form of questionnaires. While the data analysis technique uses a percentage formula.Â the results of this study about the development of the use of facebook in supporting learning activities achieve a score in the category